Using e-learning in pre-service English teacher education in Chinese fourth-tier cities: An exploratory study - Ruiqian Yang; Yiu Chi Lai (Journal of Research in Science, Mathematics and Technology Education, 2019)
Nowadays, e-learning is widely adopted in all education sectors, but different teachers utilize different strategies to teach their students. In the field of teacher education, views on the ways in which e-learning can be used are also varied. It is worth exploring how to implement e-learning in courses and how student teachers can apply the e-learning strategies they learned during their own field experience courses. A better understanding of the current practice will not only help teacher educators and student teachers to understand relevant pedagogical approaches in regard to e-learning, but will also enable student teachers to learn how to use appropriate e-learning strategies in their classes. This study explores the e-learning strategies adopted in teacher education courses for pre-service English teachers in mainland China, with a focus on Chinese fourth-tier cities. A total of 475 student teachers were involved and a mixed-method research approach was adopted. Both qualitative and quantitative data were collected via questionnaires and interviews. The findings can enhance the current understanding of the common strategies used in e-learning in English pre-service teacher education courses in Chinese fourth-tier cities. We also give some suggestions for better future e-learning pedagogical approaches.